Upaya Meningkatkan Aktivitas dan Hasil Belajar Biologi Dengan MenggunakanMetode Pembelajaran Cooperative Learning Tipe Tongkat Berjalan (Talking stick) Pada Siswa Kelas XI IPA 3 SMAN 1 Lembah Melintang (Universitas PGRI Sumatera Barat, 2015)
This research was conducted based on the problem that had been found in SMAN 1 Lembah Melintang where the learning method that applied by the teachers are still dominated by lecturing method and unstructured discussion which give impact on competency of biology learning of the student. Therefore, authors apply by cooperative learning with use Talking Stick Type. The aims of this research is to know, how far cooperative learning with use Talking Stick Type can improve students learning activity and the result in biology lesson. The type of research is action class at XIIPA3ofSMAN 1 Lembah Melintang. The implementation consist of 2 cycles are planning, implementation, observation and reflection. Techniques data analysis is carried out using the formale techniques proportion.Result of the analysis first cycle and second cycle show students learning active ty has increased for all indicators that is actively discussing increased 77,6 % in first cycle to 82,9 % in second cycle, hearing activity increased 79,6% in first cycle to 86,2 % in second cycle, to answer the questions increased 30,3% in first cycle to 43,4 % in second cycle, responding questions increased 19,1% in first cycle to 34,2% in second cycle, taking the duty in group increased 68,4% in first cycle to 74,3% in second cycle, cooperation on group increased 62,5% in first cycle to 76,3% in second cycle, Doing the duty in group increased 40,8% in first cycle, to 50,7% in second cycle. Collecting the sheet increased 53,9% in first cycle to 64,5% in second cycle.The result of evaluation the students that passed the examine increased from 22 students (57,79%) in first cycle, to 33 students (86,84%) in second cycle The result of the research learning model through Cooperative learning with use Talking Stick Typecan increase student learning activities and the result in biology class at XIIPA3 ofSMAN 1 Lembah Melintang. So this method can applied as aneffort to increase student learning activities, because there is no methods most superior from the existing method, each of them has weaknesses and advantages.